2017
DOI: 10.1371/journal.pone.0185290
|View full text |Cite
|
Sign up to set email alerts
|

Use and disuse of malaria bed nets in an internally displaced persons camp in the Democratic Republic of the Congo: A mixed-methods study

Abstract: IntroductionMalaria is a major cause of morbidity and mortality among displaced populations in tropical zones. Bed nets are widely used to prevent malaria; however, few data are available on bed net distribution within displaced populations.MethodsMixed methods study in a single internally displaced persons (IDP) camp and neighboring community in Eastern Democratic Republic of the Congo (DRC). Qualitative data (focus group discussions, FGDs) and quantitative data (door-to-door survey and individual testing usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…Factors that impeded its usage included the hours of travel necessary to reach a health center and being single, widowed, or divorced [53]. Brooks et al identified that women in DRC rarely complied with ITN use to prevent malaria except where it concerned their fetuses [54]; thus, presenting information at antenatal health centers about ITNs and their use in preventing malaria was an effective way to increase compliance. Women who did not attend antenatal visits would not have knowledge about the usefulness of bednets, since they would not be exposed to the routine information sessions held at these sites [54].…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that impeded its usage included the hours of travel necessary to reach a health center and being single, widowed, or divorced [53]. Brooks et al identified that women in DRC rarely complied with ITN use to prevent malaria except where it concerned their fetuses [54]; thus, presenting information at antenatal health centers about ITNs and their use in preventing malaria was an effective way to increase compliance. Women who did not attend antenatal visits would not have knowledge about the usefulness of bednets, since they would not be exposed to the routine information sessions held at these sites [54].…”
Section: Malariamentioning
confidence: 99%
“…Brooks et al identified that women in DRC rarely complied with ITN use to prevent malaria except where it concerned their fetuses [54]; thus, presenting information at antenatal health centers about ITNs and their use in preventing malaria was an effective way to increase compliance. Women who did not attend antenatal visits would not have knowledge about the usefulness of bednets, since they would not be exposed to the routine information sessions held at these sites [54]. Another factor that made use of bednets difficult was the space constraints in camp tents, where IDPs slept on mats, making it impossible to tuck away the bednets.…”
Section: Malariamentioning
confidence: 99%
“…The disease continues to pose global public health challenges, and its related morbidity and mortality remain significantly high in endemic countries such as Sudan. Although intensive control measures in recent years have resulted in a substantial reduction in the disease burden, the limited control options and availability of resources due to the violent conflict in Darfur maintain the high risk of malaria in displaced camps; vulnerability to malaria might be promoted by many factors including decimated health care infrastructure and social disruption, making the disease responsible for most cases of death [2]. The high prevalence of malaria in displaced populations in Africa constitutes an emerging challenge for humanitarian response as the disease becomes a serious health problem amongst internally displaced persons (IDPs) in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Lower rates of usage were however reported in a study conducted in Gulu district in Northern Uganda where only 35% of the pregnant women used ITNs [21]. This low utilisation of ITNs in Northern Uganda could be because the study was conducted in an internally displaced peoples (IDP) camp, where the exchange and selling of ITNs to meet other immediate basic needs such as food is a common practice [21,22].…”
Section: Discussionmentioning
confidence: 96%